The Effect of Using Social Media on Academic Performance of Faculty Members during Covid-19 Pandemic - Rahim, Mohammad Naim; Ali, Mohamad Bilal (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
The use of social media has increased in schools and universities due to the new norms of teaching and learning during the Covid-19 pandemic. However, this educational paradigm shift requires further surveys to explore the potentials and restrictions, particularly in the context of Afghanistan. Therefore, a quantitative method and descriptive survey design are adopted to examine the effect of using social media (Facebook, WhatsApp, and Telegram) on the academic performance (Mean Scores of GPA) of Afghanistan faculty members who are pursuing their postgraduate studies at Universiti Teknologi Malaysia (UTM). The participants are (N=103 male and female) who are randomly selected. The data is collected through a structured survey google form. Frequency and percentage statistical analysis, Independent-Samples T-test, and Independent-Measures ANOVA are performed as data analysis techniques. The results show a large number of WhatsApp users in terms of frequency and percentage among faculty members of Afghanistan who are using social media. The findings also examine that there is no significant difference between the mean scores of GPA in the academic performance of faculty members using different types of social media. In conclusion, the study contributes to establishing an in-depth understanding of the effect of using social media on the academic performance among faculty members based on the new policies of e-learning implementation by the Ministry of Higher Education during the Covid-19 pandemic.